Cognitive Appraisals of Alcohol Use in Early Adolescence: Psychosocial Predictors and Reciprocal Associations With Alcohol Use. (April 2017) - Colder, Craig R.; Read, Jennifer P.; Wieczorek, William F.; Eiden, Rina D.; Lengua, Liliana J.; Hawk, Larry W.; Trucco, Elisa M.; Lopez-Vergara, Hector I.
Early adolescence is a dynamic period for the development of alcohol appraisals (expected outcomes of drinking and subjective evaluations of expected outcomes), yet the literature provides a limited understanding of psychosocial factors that shape these appraisals during this period. This study took a comprehensive view of alcohol appraisals and considered positive and negative alcohol outcome expectancies, as well as subjective evaluations of expected outcomes. Developmental-ecological theory guided examination of individual, peer, family, and neighborhood predictors of cognitive appraisals of alcohol and use. A community sample of 378 adolescents (X ¯ age 11.5 years at Wave 1 (W1), 52% female) was assessed annually for 4 years. Longitudinal path analysis suggested that the most robust predictors of alcohol appraisals were peer norms. Furthermore, perceived likelihood of positive and negative alcohol outcomes prospectively predicted increases in drinking. There was limited support for appraisals operating as mediators of psychosocial risk and protective factors.